European Regional Integration and its Partnership with Türkiye: An Assessment of the Specific Customs Union - Saatcioglu, Cem; Celikok, Kaan (International Journal of Economics and Financial Issues, 2023)
International economic integrations, especially after the end of World War II, result from the long-term goals of establishing political unity based on countries’ orientation towards their common economic interests. Customs unions, in which states abolish tariffs among themselves and apply common tariffs to third countries, are the next advanced stage of international integration after free trade zones. While customs unions eliminate tariffs and related taxes in trade within their jurisdiction, they also establish a common external tariff. This entails some asymmetrical disadvantages for the countries within the Union. A new step by Türkiye in its efforts to integrate with the West was its application to join the EEC in 1959. The Customs Union, defined by the Ankara Agreement signed in 1963, came into effect in 1996 as a result of the agreement made at the meeting of the Association Council of 6 March 1995 adopted "Customs Union Decision". The aim of this study is to examine the bilateral trade impact of the Customs Union between Türkiye and the EU. H1: Which fields should be included in the customs union between Türkiye and the EU? H2: How will the inclusion of trade in digital goods and services in the Customs Union affect EU-Türkiye trade? The results from the analysis covering the years of 1996-2021 showed that the Customs Union has had a positive but limited effect for the trade between EU-Türkiye. The customs union needs to be updated taking into account public procurement, agriculture and digital services.